STRATEGI PENGEMBANGAN USAHATANI KOPI ARABIKA DI DESA TEPAL KECAMATAN BATULANTEH KABUPATEN SUMBAWA - Aprianti, Furna; Kurniawansyah, K; Asmini, A (Pusat Riset dan Publikasi, 2024)
This study aims to formulate strategies that can be implemented in efforts to develop Arabica coffee farming in Tepal Village, Batulanteh Sub-District, Sumbawa District. This type of research is descriptive research with a quantitative approach. The type of data used was qualitative data obtained directly from research informants using interview techniques. The informants in this study were all coffee farmers in Tepal Village, totaling 35 people. Data analysis in this study was carried out using the SWOT analysis technique. The results of this study showed that the strategy for developing Arabica coffee farming in Tepal Village, Batulanteh Sub-District is in quadrant I. The strategy that can be applied in this condition is to support an aggressive policy (growth-oriented strategy). This can be done by utilizing all the strengths and opportunities available to overcome the various weaknesses and threats faced. The results of the SWOT analysis that has been carried out produce four alternative strategies, namely SO strategy, WO strategy, ST strategy and WT strategy. However, the alternative strategy that is a priority in efforts to develop Arabica coffee farming in Tepal Village, Batulanteh District is to implement the SO strategy which is implemented by utilizing the strengths owned to be able to optimize all existing opportunities. The alternative strategies produced are: 1). Increase the quantity and quality of production by utilizing all available resources, and 2). Expand the marketing network by utilizing technological advances in the field of information and communication.